Athlete atypicity on the edge of human achievement: Performances stagnate after the last peak, in 1988 - Berthelot, G.; Tafflet, M.; El Helou, N.; Len, S.; Escolano, S.; Guillaume, M.; Nassif, H.; Tolaïni, J.; Thibault, V.; Desgorces, F. D.; Hermine, O.; Toussaint, J.-F. (PLOS ONE, 2010)
The growth law for the development of top athletes performances remains unknown in quantifiable sport events. Here we present a growth model for 41351 best performers from 70 track and field (T&F) and swimming events and detail their characteristics over the modern Olympic era. We show that 64% of T&F events no longer improved since 1993, while 47% of swimming events stagnated after 1990, prior to a second progression step starting in 2000. Since then, 100% of swimming events continued to progress.